Markov-based availability analysis of clusters for distributed rendering system - HONG Zhi-guo1; WANG Yong-bin1; SHI Min-yong2 (Tongxin xuebao)
The availability of system comprising multiple cluster nodes in the case of CMF was studied.Firstly,contraposing to the system with two cluster nodes,two CTMC models for the step-by-step recovery mechanism and uniform resetting one were proposed respectively.Furthermore,the conclusion on the priority and inferiority comparison for related plans of different mechanisms was derived thereby.Moreover,its correctness was simulated and validated by stochastic reward nets tool.Additionally,the availability of system with n（n>2） cluster nodes was discussed.